Shallow geothermal energy systems for district heating and cooling networks: Review and technological progression through case studies - Figueira, João S.; García Gil, Alejandro; Vieira, Ana; Michopoulos, Apostolos K.; Boon, David P.; Loveridge, Fleur; Cecinato, Francesco; Götzl, Gregor; Epting, Jannis; Zosseder, Kai; Bloemendal, Martin; Woods, Michael; et al. (My University, 2024)
Heating and Cooling constitute a major part of society's final energy use and a significant contributor to greenhouse gas emissions. The world society ought to mitigate climate change through decarbonisation, which must include the transition to low-temperature, sustainable and renewable heating and cooling technologies. Shallow Geothermal Energy is one of the most energy efficient and least greenhouse gas emitting available alternatives to provide space heating and cooling. The decarbonisation of the heating and cooling sector may have to comprise both individual systems and shared electrified heating and cooling systems from renewable sources of energy, where economies of scale and synergies between different types of consumers can be exploited. To this end, the focus of this paper is on the integration of shallow geothermal energy technologies into district heating and cooling systems. A key contribution of this work is the illustration of a number of practical case studies, highlighting the potential of existing shallow geothermal systems for DHC networks, which, as front runners in adopting such technologies, serve as paradigms for future development. Follows a discussion providing an outlook over the next 25 years. All in all, the future of utilizing shallow geothermal energy for district heating and cooling seems to be promising to play a pivotal role in sustainable urban development and decarbonizing the heating and cooling sector.
Keywords: Shallow geothermal energy; District heating and cooling; 5GDHC; Low-temperature district heating networks